Numerical Simulation of Electrochemical Processes at a Tubular Electrode. Application to Spectroscopy - Klymenko, O. V. V.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 2008)
A model of spectroelectrochemical cell design based on a tubular working electrode with optical fibers connected to a spectrometer entering it from two ends is built. Both current and absorbance responses of the cell are numerically simulated and the operation regimes are determined in terms of ranges of governing parameters for chronoamperometry and linear sweep voltammetry.
Keywords: numerical simulation; tubular electrode; spectroelectrochemistry; absorbance